Interpreting the Viking Age to Medieval Period Transition in Norse Orkney through Cultural Soil and Sediment Analyses - Ian A. Simpson; Karen B. Milek; James H. Barrett
The transition from the Viking Age (ca. A.D. 800–1050) to the Medieval period (ca. A.D. 1050–1500) saw the development of widening trade activities that incorporated peripheral North Atlantic polities into mainstream Europe and contributed to the intensification of marine-resource exploitation and agricultural production in these localities. As yet, there is only lim-ited understanding of these intensification processes and their interrelationships, particularly at a local, site-based level. Through the micromorphological analysis of cultural soils and sed-iments at Quoygrew, Westray, Orkney, we explore the characteristics of farming and fishing activ-ity during the Viking Age–Medieval transition period and establish their chronological rela-tionships. The study demonstrates: (1) that intensification took place from ca. A.D. 966–1162 on an already existing Viking Age settlement, (2) that intensification of fishing activity occurred prior to the intensification of arable agriculture, and (3) that the Quoygrew site continued throughout this period as an economically diverse permanent settlement. When viewed in a wider North Atlantic context, these findings indicate that intensification of different economic activities proceeded at different rates and that intensification of specialized economic activi-ties during the transition from the Viking Age to the Medieval period was dependent on exist-ing knowledge of local environments. © 2005 Wiley Periodicals, Inc.